Pharmacotherapy of cognitive deficits in schizophrenia. (8th November 2013) - Opler, Lewis A.; Medalia, Alice; Opler, Mark G.; Stahl, Stephen M.
<x content-type="archive" xml:space="preserve">Abstract</x> While second-generation antipsychotics treat negative as well as positive symptoms, recovery for persons with schizophrenia remains elusive, in part because there are no FDA-approved medications that treat the cognitive deficits of schizophrenia (CDS). Recent work has identified agents that, when added to antipsychotics, improve cognition in schizophrenia. This work and hypothesized mechanisms of action will be reviewed.